WIRELESS MSEB METER READING VEHICLE - MR. VISHAL VINAYAK KADAM; MR. GANESH GOVARDHAN MERGU; MR. JUBER JAFAR JAMADAR; MR. IMRAN ILIYASAHMED SHAIKH; PROF. ZUBAIR ABDUL REHMAN SHAIKH (International Journal of Innovations in Engineering Research and Technology, 2019)
The main goal of the paper is to suggest a design that can send meter reading wirelessly which in turn will be effective in billing. It basically proposes an idea of a vehicle having RF receiver that can take readings from all energy meters installed at consumer’s premise. Each meter will have a microcontroller and RF module. The microcontroller will take reading continuously from the energy meter and it will transmit the same along with Meter ID continually by using RF transmitter. When the MSEB vehicle will pass through the RF transmitter range the RF transmitter in the meter will transmit the current meter reading to MSEB vehicle’s RF receiver. MSEB vehicle RF will obtain that reading and it will send it to the microcontroller for saving and future billing process.